The Effect of Electronic Payment Systems on Revenue Collection of Water Utilities in Uganda: A Case of National Water and Sewerage Corporation (Nwsc) - Kabale Branch - Grace, Atuheire (Kabale University, 2022)
A Research Dissertation Submitted to Kabale University in Partial Fulfilment of the Requirements for the Master’s Degree of Business Administration